A Validation of the Group-Based Medical Mistrust Scale in Formerly Incarcerated Black and Latino Men - Valera, Pamela (Am J Mens Health, 2016)
While there is a growing body of literature on medical mistrust and its relevance to public health, research on formerly incarcerated Black and Latino men and their perception of mistrust toward medical providers and medical institutions remains scant. Very little is known about whether formerly incarcerated Black and Latino men mistrust medical and clinical providers given their previous experiences with the criminal justice system. It is important to determine whether medical mistrust play a key role in the health and health behaviors of released Black and Latino men. The purpose of this study is to validate and assess the psychometric properties of the Group-Based Medical Mistrust Scale for use among formerly incarcerated Black and Latino men in New York City. The findings of the exploratory and confirmatory factor analyses state that a two-factor structure fit the data best. Two dimensions emerged as important subscales: discrimination and suspicion. The current findings suggest the two-factor Group-Based Medical Mistrust Scale is a valid and reliable assessment tool to discern medical mistrust levels among formerly incarcerated Black and Latino men.